Photocatalytic direct C–S bond formation: facile access to 3-sulfenylindoles via metal-free C-3 sulfenylation of indoles with thiophenols. Issue 60 (31st July 2017) - Guo, Wei; Tan, Wen; Zhao, Mingming; Tao, Kailiang; Zheng, Lv-Yin; Wu, Yongquan; Chen, Deliang; Fan, Xiao-Lin
Abstract : An efficient and convenient photocatalytic direct C-3 sulfenylation of indoles with thiophenols has been developed for the construction of 3-sulfenylations. Abstract : An efficient and convenient photocatalytic direct C-3 sulfenylation of indoles with thiophenols has been developed for the construction of 3-sulfenylations. This protocol employs thiophenols as the sulfenylating agents, inexpensive rose bengal as the photocatalyst, and shows mild conditions, readily available starting materials, high atom and step atom economy, and environmental advantages. The representative method provides a straightforward approach for C–S bond formation, and has potential applications in the chemical and pharmaceutical industries.